Telemedicine in Malaysia: ethical aspects on utilising teleconsultation for patient care / Muhamad Zaid Muuti - Muuti, Muhamad Zaid (2019)
Clinic consultations for patients traditionally involve the physician taking a detailed history, performing a physical examination, and occasionally ordering laboratory investigations. These three elements are essential components that help the physician to formulate diagnoses for patients in order to prescribe appropriate treatment. Technological advancements have vastly improved the field of telemedicine resulting in teleconsultations currently being easily accessed by patients through mobile phone applications. However, physicians are not able to perform physical examinations through these teleconsultations, resulting in ethical concerns regarding this practice. In addition, the Telemedicine Act (Malaysia) 1997 has yet to be enforced. This dissertation will briefly explore the development of telemedicine in Malaysia to allow us to understand the motivations behind its introduction. Following that, four local telemedicine platforms will be examined to enable us to deliberate whether teleconsultation without physical examination can be justified. We will discover that the practice is ethically and legally permissible in the US, UK and Singapore under strict conditions that the same standard of care is delivered, and patients are fully informed of the risks. Subsequently, we will learn that while teleconsultation can improve access to healthcare, the terms and conditions imposed by the local telemedicine platforms can erode patient’s autonomy and limit their rights to seek compensation; which could render the practice as unethical. Afterwards, we will discover that despite the lack of guidelines and legislation pertaining to teleconsultation practice in Malaysia, medical practitioners and telemedicine platforms still have ethical duties towards the patients. The dissertation concludes with a recommendation that a guideline in teleconsultation is introduced to ensure it to be practiced ethically.